Diagnostic importance of hepatocyte nuclear factor 1 beta (HNF1β) in testicular tumors and its sensitivity for the detection of yolk sac tumors: an immunohistochemical analysis - Arslan, Remzi (The European Research Journal, 2022)
Objectives: Testicular tumors are common solid malignancies in young fertile men, and most are germ cell tumors. In general, they originate from a single germ cell and transform into different tumor types or present with the coexistence of different morphological patterns. Due to the heterogeneity of these tumors, immunohistochemical markers are frequently used in their differential diagnosis. In recent years, some studies have indicated hepatocyte nuclear factor 1 beta (HNF1β) can be used in the differential diagnosis of testicular tumors, especially yolk sac tumors (YSTs). In this study, we aimed to investigate the general expression status of HNF1β in all testicular tumors and determine its importance in YST detection. Methods: A total of 144 testicular tumors treated with orchiectomy between 2011 and 2020 were included in our study. The pathological diagnosis reports of these cases were retrospectively reviewed and their general prognostic features were determined. HNF1β immunohistochemical staining was applied to the characteristic paraffin blocks representing the lesions. Staining was evaluated in terms of severity and prevalence. Results: Most cases (38.2%) were seminomas, followed by mixed germ cell tumors (34.0%, 49/144), embryonic carcinomas (7.6%), pure YSTs (4.9%), and others (Leydig cell tumors, mesenchymal tumors, lymphomas, etc.). No HNF1β immunostaining was observed in any of the seminomatous lesions. A high level of staining was present in almost all the pure YSTs and tumor areas with the YST component. HNF1β had a specificity of 95.1% and sensitivity of 87.1% in the detection of YSTs. Conclusions: HNF1β has high specificity and sensitivity in detecting YSTs among testicular tumors, and therefore we consider that it can be routinely used to detect the presence of YSTs, especially in patients with mixed germ cell tumors.